2022
DOI: 10.1088/1361-665x/ac4ab4
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent circuit modeling and analysis of aerodynamic vortex-induced piezoelectric energy harvesting

Abstract: Low-speed wind energy has potential to be captured for powering micro-electro-mechanical systems or sensors in remote inaccessible place by piezoelectric energy harvesting from vortex-induced vibration (VIV). Conventional theory or finite-element analysis mostly considers a simple pure resistance as interface circuit because of the complex fluid-solid-electricity coupling in aeroelastic piezoelectric energy harvesting. However, the output alternating voltage should be rectified to direct voltage to be used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Then, the energy is stored in energy storage devices such as supercapacitors or rechargeable batteries. In order to improve the conversion efficiency of the energy harvesting device, researchers have made a large number of optimization designs in electrical and mechanical perspective [62]. The energy harvesting system generates alternating current (AC) and requires AC-direct current (DC) to be converted into DC in load circuits.…”
Section: Energy Conversion Efficiency Optimization Strategymentioning
confidence: 99%
“…Then, the energy is stored in energy storage devices such as supercapacitors or rechargeable batteries. In order to improve the conversion efficiency of the energy harvesting device, researchers have made a large number of optimization designs in electrical and mechanical perspective [62]. The energy harvesting system generates alternating current (AC) and requires AC-direct current (DC) to be converted into DC in load circuits.…”
Section: Energy Conversion Efficiency Optimization Strategymentioning
confidence: 99%
“…Song et al [43] showed an energy harvester used in water surface scene, both theoretical and experimental results showed that lighter and larger cylinder could lead to better output performance. Jia et al [44] proposed an equivalent circuit modelling method to system-level simulate vortex-induced energy harvesters. There were three circuit equations corresponding to three circuit loops.…”
Section: Introductionmentioning
confidence: 99%